Gender identity-based biases in judgments of social pain - Figueiredo, Camilla Vieira de (2024)
Adverse social experiences pose a threat to health and well-being by eliciting social pain in individuals. Previous research has indicated biases in social pain judgments toward members of different social groups. These findings suggest that socially valued ingroups are perceived as more sensitive to social pain compared to socially devalued outgroups. However, this effect raises a critical question, as pain is a negative attribute and individuals avoid painful situations. Thus, attributing more social pain to the ingroup challenges individuals’ motivation for positive distinctiveness (i.e., the tendency to provide positive attributes to the ingroup). This suggests that social pain may encompass different meanings depending on the dimensionality of social comparison present in intergroup relations. Building on this premise, we developed a research program to address the hypothesis of the multiple meanings of social pain and its influence on social pain judgments regarding cisgender and transgender individuals. Our thesis posits that cisgender individuals will attribute more social pain to transgender targets than to cisgender targets when the social comparison dimension between these groups is based on the social value of identity belongings. In this dimension, social pain is expected to assume its originally negative symbolic meaning, reflecting the social devaluation of transgender identity (i.e., the symbolic dimension of social pain). Paradoxically, when the social comparison dimension involves obtaining resources for addressing social pain (e.g., receiving professional mental health assistance), cisgender individuals will attribute less social pain to transgender targets (vs. cisgender targets). In this case, social pain is expected to serve a utilitarian function in securing greater access to support resources for the ingroup (i.e., the utilitarian dimension of social pain). In addition to providing a literature review on social pain and biases in social pain judgments in hierarchized intergroup relations, we discuss the implications of social pain meanings in the dynamics of cisgender-transgender relationships, a relatively understudied area in social psychology (Chapter 1). Our research program includes four empirical studies organized into four empirical chapters (Chapters 2-5). Initially, we assessed the attribution of social pain to cisgender and transgender targets in a symbolic dimension. We demonstrated that cisgender individuals attribute more social pain to transgender individuals (vs. cisgender individuals), especially transgender women (Chapter 2), and that this attribution is related to the social devaluation of transgender identity (Chapter 3). When we increased (vs. decreased) the social value of transgender identity, we observed a reduction in social pain bias (Chapter 4). We found that the social pain bias occurs exclusively for targets with male-assigned birth sex (i.e., transgender women and cisgender men) and provided evidence that social pain can serve as a mechanism to express the stigmatization of transgender women. In Chapter 5, we added evidence to the hypothesis of the variable meanings of social pain by investigating whether the attribution of social pain to transgender women and cisgender men is influenced by the social comparison dimension (symbolic vs. utilitarian) in which social pain is assessed. We also examined the relationship between social pain and the attribution of professional support to targets. Overall, the results supported our hypothesis, revealing greater attribution of pain and support to transgender women only when health assistance resources were not salient (i.e., in the symbolic condition). Finally, in Chapter 6, we provide a general discussion and concluding remarks on the research conducted in this thesis, including the limitations of our research program and suggestions for future investigations in this line of research. This research program provides the first experimental evidence that social pain can assume different meanings in the context of hierarchized intergroup relations. The social pain bias may potentially impact mental health support for stigmatized outgroup members, such as transgender women. These findings contribute to the investigation of social pain by presenting unexplored mechanisms and functions of social pain, particularly in the complex landscape of gender identity-based intergroup relations. They help understand the dynamics of these relationships and have potential implications for intervention and treatment of social pain in transgender individuals.